2016
DOI: 10.1186/s12903-016-0315-8
|View full text |Cite
|
Sign up to set email alerts
|

Dental age assessment in 6- to 14-year old German children: comparison of Cameriere and Demirjian methods

Abstract: BackgroundThe aim of the study was to compare two frequently used dental age estimation methods for accuracy.MethodsA total of 479 panoramic radiographs in age groups 6–14 years from a German population were evaluated. The dental age of 268 boys and 211 girls was assessed by means of the method of Demirjian (1973) and Cameriere (2006) and compared with their actual chronological age.ResultsDemirjan’s method showed an overestimation of dental age compared to chronological age in all age groups for boys (mean di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
1
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 33 publications
5
21
1
8
Order By: Relevance
“…According to the study done by Wolf TG etal in 2016, the mean difference between chronologic age and dental age using Demirjian’s method for boys and girls were –0.6 and –0.18 respectively and by Cameriere’s method were 0.07 and 0.08. Cameriere’s method showed slight underestimation of real age 6 which is consistent to our result showing an underestimation by Cameriere’s method. When the individual age groups were analyzed in their study, Demirjian’s method showed an overestimation of age compared to the chronologic age in all age groups for boys (mean difference= –0.16, P=0.010) and for girls there was an overestimation of age except for one age group (8 and 13) (mean difference= –0.18, P=0.008).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…According to the study done by Wolf TG etal in 2016, the mean difference between chronologic age and dental age using Demirjian’s method for boys and girls were –0.6 and –0.18 respectively and by Cameriere’s method were 0.07 and 0.08. Cameriere’s method showed slight underestimation of real age 6 which is consistent to our result showing an underestimation by Cameriere’s method. When the individual age groups were analyzed in their study, Demirjian’s method showed an overestimation of age compared to the chronologic age in all age groups for boys (mean difference= –0.16, P=0.010) and for girls there was an overestimation of age except for one age group (8 and 13) (mean difference= –0.18, P=0.008).…”
Section: Discussionsupporting
confidence: 91%
“…The comparison shows an advantage for both genders. 6 Our study also showed an underestimation of age by Cameriere’s method. However, we have not grouped the patients according to age or gender.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Por otro lado Wolf et al, en el año 2016 utilizaron los métodos de Cameriere y método de Demirjian; en el método de Demirjian mostraron una sobreestimación de la edad dental en comparación con la edad cronológica en todas las edades del grupo de niños en un rango -0,35 a 0,09 años; por otro lado, mientras que el grupo de niñas presento una subestimación en un rango de -0,45 a 0,13 años (14). En nuestro estudio el grupo de niñas en su mayoría tuvo sobreestimación y su rango fue de 0,24 a 0,98 años y una subestimación de -0,69 en varones se presentó igualmente una sobreestimación en la mayoría de los grupos etarios y los rangos fueron de 0,33 a 1,51 años y la subestimación de -0,65 años.…”
Section: Resultsunclassified
“…Ecuador no evidencia estudios que hayan estimado la edad dental con el método de Demirjian, siendo este el primero en presentarse, conjuntamente con una muestra considerable (617 radiografías panorámicas) en relación a otros estudios realizados en otros países (9,12,14,15,17,18).…”
Section: Resultsunclassified